Solitary: the inside story of supermax isolation and how we can abolish it - Kupers, Terry Allen (University of California Press, 2017)
Supermax isolation -- A culture of punishment -- Race matters a lot -- The decimation of life skills -- Adding madness to the mix -- Women do not do well in solitary -- Youth in isolation -- The SHU post-release syndrome -- A rehabilitative attitude -- Mental health care in corrections -- The disruptive prisoner -- Beyond supermax isolation